ВИЗНАЧЕННЯ ВПЛИВУ ЗМІНИ МЕЖ ДІАПАЗОНУ ВХІДНОЇ НАПРУГИ НА ПОТУЖНІСТЬ ТРАНСФОРМУЮЧОГО ЕЛЕМЕНТА СТАБІЛІЗАТОРА НАПРУГИ З ТРАНСФОРМАТОРНО-КЛЮЧОВОЮ ВИКОНАВЧОЮ СТРУКТУРОЮ - Липківський, К.О.; Можаровський, А.Г. (Інститут електродинаміки НАН України, Київ, 2019)
In the transformer-and-switches executive structure (TSES) selected for the AC voltage stabilizer, a transforming element (TE), which has a sectioned winding, it is possible, if necessary, to change the array of transmission coefficients as necessary by means of a certain reconfiguration. The need for this may be due in particular to the variation of theboundaries of a given range of changes in the input voltage of the stabilizer. In the work, the influence of such variation on the installed capacity of the transforming element of the TSES is investigated and the possibility of increasing the efficiency of using TE while maintaining its thermal state within pretermined (predetermined) limits is substantiated.This allows you to either choose a smaller size of the TE core or increase the allowable power of the load.References 15, tables 3, figures 5.